Characteristics, sources and health risks of toxic species (PCDD/Fs, PAHs and heavy metals) in PM2.5 during fall and winter in an industrial area. (January 2020) - Bi, Chenglu; Chen, Yantong; Zhao, Zhuzi; Li, Qing; Zhou, Quanfa; Ye, Zhaolian; Ge, Xinlei
Abstract: Particulate toxic species, such as polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs), polycyclic aromatic hydrocarbons (PAHs) and heavy metals may have significant health risks. This study investigated characteristics, sources and health risks of all three classes of toxic species in PM2.5 (particles with aerodynamic diameter ≤2.5 μm) samples collected at an industrial area in Changzhou, a big city in the Yangtze Delta region of China. Fourteen heavy metals altogether constituted 2.87% of PM2.5 mass, with Fe, Al and Zn as the major elements. Principal component analysis (PCA) suggested that heavy metals came from four sources: vehicles, industry, crustal dust, mixed coal combustion and industrial process. The daily average concentration of 18 PAHs was 235.29 ng/m 3, accounting for 0.21% of PM2.5 mass. The dominant PAHs were high molecular weight ones, contributing 73.5% to the total PAHs. Diagnostic analyses indicated that sources of PAHs included vehicle/coal combustion and petroleum emissions, wherein diesel emission played a more important role than gasoline emission. PCA showed that the largest contributor of PAHs was vehicle exhaust mixed with coal combustion, followed by three industry-related sources. Total concentration of 17 PCDD/Fs varied between 3.14 and 37.07 pg/m 3, with an average of 14.58 pg/m 3 . The 10 PCDFs accounted for 70.5% of total concentration of 17 PCDD/Fs. Health risk assessments showed that the carcinogenic risk of heavy metals was acceptable, while risks from PAHs and PCDD/Fs cannot be ignored. Back trajectory analysis indicated that local/regional transported air masses from northern China was the major source areas of the toxic species. Graphical abstract: Image 10631 Highlights: Concentrations and sources of toxic species including heavy metals, PAHs and PCDD/Fs were determined. Diagnostic ratio of PAHs revealed diesel emission contributes more than gasoline emission. PAHs and PCDD/Fs are assessed to have high health risks to residents in this area.